Management of Education and Education Personnel in Aligning the Digital Era with Islamic Values - Mulia, Ezi; Ilmi, Darul; Yakub Simbolon, Ali Mustopa; Yanti, Ira; Sumarni, Weni (GIC Proceeding, 2023)
The era of digitalization is a very real effort that will be faced by educational institutions now marked by technological advances on the side of demands for quality development that has taken place, so that the achievement of social and cultural changes in the school community is significant. So that from this problem education must be in managerial education that is able to respond to the direction of change. So that education management based on digitalization is an important effort that must be encouraged as the future strength of the institution and the adequate quality of its human resources. Immediate polishing of education management and educational staff towards digitization. Advances in technology and information are very important in the strategic aspects of digitizing learning, digitizing infrastructure, digital-based administration and changing local culture towards a useful international based on digital culture. to penetrate educational changes in a more appropriate direction in the era of the industrial revolution 4.0. Because this is a demand in the world of education today that must be considered properly and carefully. From this research, there are several things suggested in facing the digital era, namely the need for changes in the application of systems in educational institutions towards digital transformation, in addition to core competencies, teaching staff are also required to have a qualification and supporting competencies including: agility, innovation, creativity, anticipation, experimentation, openness thoughts, and networking. With this, all management of educational institutions and educational staff in this digital era can be carried out in accordance with the expectations of all parties and in harmony with Islamic religious values.